The Effect of Leverage and Liquidity on Firm Value with Profitability as an Intervening Variable in Retail Trading Companies Listed on the Indonesian Stock Exchange in 2016-2019 - Syahrizal Chalil (Outline Journal of Management and Accounting, 2022)
The purpose of this study was to determine the effect of leverage and liquidity on firm value through profitability in retail trading companies. Sampling was taken using purposive sampling method. There are 21 trading companies listed on the Indonesian stock exchange during the period 2016 – 2019. The analytical technique used in this study is the Partial Least Square (PLS) analysis technique using SmartPLS 3.0 software. The results of this study indicate that leverage has a negative and significant effect on firm value and has a negative and significant effect on profitability. Liquidity has a negative and significant effect on firm value and has a significant effect on profitability. Profitability has a significant effect on firm value and profitability is not able to mediate the effect of leverage and liquidity on firm value.